Investigation of the process of obtaining extracts from vegetable raw materials and their use in cheese production - E. P. Suchkova; R. Hussaineh (Новые технологии)
The process of obtaining aqueous plant extracts from spicy-aromatic, spicy-flavor plants, their use in the production of cheese to form specific taste properties and preserve original characteristics of cheese mass have been studied. Extracts from different aromatic herbs: rosemary, cumin, thyme, oregano and their composition, as well as cow milk (mass fraction of fat 3.2%); bacterial leaven, rennet enzyme, cheese mass with extracts after aging for 24 hours are the objects of the research. Aqueous extracts were prepared at different parameters (different doses, duration of exposure). The following organoleptic parameters were determined in the extracts: taste, smell and color in accordance with the developed 5-point scale, physicochemical parameters, dry matter content using a refractometer, the pH of the extract by potentiometric method using a pH meter. Prepared samples of extracts were added to the ready-to-form cheese grain, the amount of added extract varied from 2,5 to 7,5%. After the introduction of plant extracts into the cheese mass, its organoleptic and physicochemical parameters were determined, such as: active pH acidity, mass fraction of moisture, mass fraction of fat. It was found that the extracts of cumin and oregano herbs showed better results in organoleptic characteristics in comparison with extracts of rosemary and thyme. Cheese mass with the addition of plant extracts from the composition of cumin and oregano herbs also had the best organoleptic characteristics. The stage of introduction of extracts into the cheese mass was determined. The extracts were added to the mass before molding. The effect of plant extracts on the storage capacity of cheese mass for 7 days was also studied: the use of extracts from the composition of cumin and oregano preserved the original characteristics of cheese better than extracts from the composition of rosemary and thyme.